Pengembangan Ekonomi Masyarakat Melalui Pemberdayaan Ekonomi Mikro Kecil dan Menengah di Kelurahan Penajam - Nadi Hernadi Moorcy; Tamzil Yusuf; Pudjiati Pudjiati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2020)
The Micro, Small and Medium Enterprises (MSME) sector has an important role in driving the growth of the Indonesian economy. MSME contributes to a number of business entities in Indonesia and has a share in employment. In a business study is needed about the feasibility of the business. But in reality the business owner is only focused on the income and sustainability of his business. That is why community development using social assistance methods needs to be done to help solve the problems being faced. Community development contains efforts to increase participation and a sense of belonging to the programs implemented. Empowerment refers to the ability of people, especially weak groups to have access to productive resources that enable them to be able to increase their income and participate in the process of development and decision making. The results of this dedication show that the economic potential in Penajam Sub-district, Penajam District, North Penajam Paser Regency is the food industry, handicraft industry, restaurants and restaurants and MSMEs. Supporting factors in community development in the economic sector include natural resources and abundant human resources. While the limiting factors are limited capital, facilities and infrastructure as well as low community participation.